Rafael Estrada and his distinction within the literary field in Costa Rica in the 1920s - Rodríguez Cascante, Francisco (2017)
Based on the theoretical statements by Pierre Bourdieu regarding cultural fields, I analyze the problem argued by Rafael Estrada Carvajal in the 1920s with those agents whom possessed the greatest cultural knowledge in regards to literature in those times; he was the first poet to introduce the state-of-the-art (Vanguard) literature in Costa Rica. It is argued that in the fight for power of distinction, the literary works by the young writer, given that it was characterized by a heterogeneity which dialogued with the modernist tradition as well as with the Vanguard ones, hence stayed detached from the traditional canon; it was given to a peripheral realm in the literary world, a displacement which is true to this day.